Spatial and temporal grey water footprints of agricultural pesticide use: Improved pesticide use options to decrease water pollution in China - J. Yi; P.W. Gerbens-Leenes; M.M. Aldaya (Energy Nexus)
Pesticides cause environmental and health risks. This study estimates the spatial-temporal dynamics of water pollution by pesticides and strategies for improvement. It uses the grey water footprint (WF) to identify the most polluting crops, hotspots and periods of increased water pollution with China as the case study area. It also proposes a temporal grey WF dimension due to pesticide degradation. The study used agricultural information for the period 2011–2015 from farmer surveys. The results showed that grey WFs were three times larger in summer than in winter. Hotspots were the North China Plain and Northeast China. Maize with herbicide (acetochlor) and insecticide (cypermethrin) use contributed most. In winter, the grey WFs in Southern regions were dominated by fungicide mancozeb use for vegetables and fruits. The temporal analysis of the grey WF due to pesticide degradation shows that the maximum daily grey WF was 66 % smaller than values based on the traditional calculation method. Moreover, replacing the most polluting pesticides, mancozeb, cypermethrin and acetochlor, can contribute to 20∼90 % of grey WF reduction across regions and months. Agriculture and policymakers can use this information to reduce pesticide-related water pollution.